Images of traditional African religions in surveys of world religions - Lewis, James R. (Religion, 1990)
[Genuine] knowledge of another culture is possible [but] the student must feel that he or she is answerable to and in uncoercive contact with the culture and the people being studied. [In the past], most of what the West knew about the non-Western world it knew in the framework of colonialism; the European scholar therefore approached his subject from a general position of dominance, and what he said about this subject was said with little reference to what anyone but other European scholars had said.
paid
Keywords: Religion – Textbooks